Ex vivo observation of Pythium insidiosum-antigen treated neutrophils on three Pythium insidiosum strains isolated from vascular pythiosis patients - Sadeep Medhasi; Apichaya Sriwarom; Nitipong Permpalung; Pattama Torvorapanit; Rongpong Plongla; Ariya Chindamporn; Navaporn Worasilchai (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTThe mechanisms of Pythium insidiosum-antigen (PIA) immunotherapy activating a patient’s immune system are unknown. We evaluated the interleukin-8 (IL-8) serum levels during P. insidiosum infection and after vaccination with PIA in vascular pythiosis cases. Furthermore, we studied the anti-P. insidiosum activity of neutrophils stimulated with various concentrations of PIA ex vivo in 3 strains of P. insidiosum isolated from vascular pythiosis patients. IL-8 serum levels were evaluated using the ELISA technique. We assessed the effect of PIA-stimulated neutrophils on the viability of zoospores using MTT assay, visualized neutrophil extracellular trap (NET) formation via microscopy, and measured the levels of double-stranded DNA (dsDNA) using PicoGreen dsDNA quantitation assay in 3 strains of P. insidiosum isolated from vascular pythiosis patients. Serum levels of IL-8 gradually lowered from the early to the end phases of vaccination with PIA among the surviving group of vascular pythiosis cases. Neutrophils stimulated with 0.01 µg/ml PIA reduced zoospore viability significantly compared to PIA-unstimulated neutrophils for strain 1 and strain 3 (p < .05). Neutrophils stimulated with 0.01, 0.1, 1, and 10 µg/ml PIA exhibited significantly lower zoospore viability than PIA-unstimulated neutrophils for strain 2 (p < .05). IL-8 can be used as a biomarker for monitoring vascular pythiosis cases treated with the PIA vaccine. Also, anti-P. insidiosum activity of PIA-stimulated neutrophils was probably due to the disruption of cellular activity in zoospores rather than the mechanisms based on the formation of NETs.